Maternal NAT10 orchestrates oocyte meiotic cell-cycle progression and maturation in mice - Xue Jiang; Yu Cheng; Yuzhang Zhu; Caoling Xu; Qiaodan Li; Xuemei Xing; Wenqing Li; Jiaqi Zou; Lan Meng; Muhammad Azhar; Yuzhu Cao; Xianhong Tong; et al. (Nature Communications, 2023)
Abstract In mammals, the production of mature oocytes necessitates rigorous regulation of the discontinuous meiotic cell-cycle progression at both the transcriptional and post-transcriptional levels. However, the factors underlying this sophisticated but explicit process remain largely unclear. Here we characterize the function of N-acetyltransferase 10 (Nat10), a writer for N4-acetylcytidine (ac4C) on RNA molecules, in mouse oocyte development. We provide genetic evidence that Nat10 is essential for oocyte meiotic prophase I progression, oocyte growth and maturation by sculpting the maternal transcriptome through timely degradation of poly(A) tail mRNAs. This is achieved through the ac4C deposition on the key CCR4-NOT complex transcripts. Importantly, we devise a method for examining the poly(A) tail length (PAT), termed Hairpin Adaptor-poly(A) tail length (HA-PAT), which outperforms conventional methods in terms of cost, sensitivity, and efficiency. In summary, these findings provide genetic evidence that unveils the indispensable role of maternal Nat10 in oocyte development.